International development cooperation today : emerging trends and debates - Luchsinger, Gretchen (NGLS New YorkUS, 2008)
Sees the need for a renewed focus on improving the system of international development cooperation towards the achievement of human development goals, including through broad-based, multilateral debate reflecting diverse perspectives. Notes that the United Nations is one forum where this can happen.